Perancangan Desain Sistem Pengelolaan Pantai Berbasis Website dengan Metode UML - Adinda Rahmanda Putri; Nurhaliza Meilinda Iswanto; Eggy Fawas Ihsan (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
The management of tourist attractions and public facilities has undergone a significant transformation in recent years in line with technological developments. Previously, management was carried out manually by involving a lot of labor and human resources to maintain and manage its operations. However, digitalization has changed the way management is more efficient and organized. Digital-based systems are now widely applied to facilitate visitor access while increasing the effectiveness of tourist attraction management. Digitalization aims to create a mutually beneficial relationship between managers and visitors through an optimally designed system. This study aims to analyze the design and design of the digital management system applied to Dalegan Beach in Gresik Regency, East Java. This system is expected to be able to simplify the administrative process, improve the visitor experience, and optimize the management of existing resources. Through a systematic approach, this research explores the functional and technical needs to create effective technology-based solutions. The implementation of this system is expected to be an example of the application of digitalization in the management of other tourist attractions, so that it can support the development of the tourism sector and increase competitiveness in an increasingly competitive industry.